Expertise: A report and a manifesto. (August 2015) - Bassett, Caroline; Fotopoulou, Aristea; Howland, Kate
This article explores the stakes of digital transformation through a consideration of digital expertise. Expertise is investigated as it operates in everyday situations – drawing on empirical research undertaken in Brighton, UK, as part of the Communities and Cultures Network+ project. It is also deployed as a heuristic for inquiry into questions of use and the policy of use and investigated in relation to questions of automation that provoke reconsideration of the role of humans and machines in circuits of expertise. This latter necessitates reconsideration of how expertise can be theorized, and this is developed through an account that insists on the importance of both the material and the circulating imaginary for understanding the operations of digital expertise. Drawing these together to develop a new understanding of the economy of digital expertise, inspiration is finally drawn from earlier attempts to develop new models of technological expertise in the context of public science, undertaken with the specific intent of contributing to furthering the democratization of knowledge. In this article too, expertise is invoked albeit in a rather different way as constituting the grounds for the development of a political demand. The article closes with a question concerning the stakes of a demand for digital expertise.